Rút gọn biểu thức sau với x ≥ 0: 3 $\sqrt[]{2x}$ – 5 $\sqrt[]{8x}$ + 7$\sqrt[]{18x}$ +28

Rút gọn biểu thức sau với x ≥ 0:
3 $\sqrt[]{2x}$ – 5 $\sqrt[]{8x}$ + 7$\sqrt[]{18x}$ +28

Share

1 Answer

  1. Lời giải:

    Với x ≥ 0 thì các căn trong biểu thức có nghĩa

    3$\sqrt[]{2x}$ -5 $\sqrt[]{8x}$ +7 $\sqrt[]{18x}$ +28

    =3$\sqrt[]{2x}$ – 5 $\sqrt[]{2^{2}.2x}$ + 7 $\sqrt[]{3^{2}.2x}$+28

    =3$\sqrt[]{2x}$ -10 $\sqrt[]{2x}$ +21 $\sqrt[]{2x}$ +28

    =14$\sqrt[]{2x}$+28

    • 0
Leave an answer

Leave an answer

Browse

Rút gọn biểu thức sau với x ≥ 0: 3 $\sqrt[]{2x}$ – 5 $\sqrt[]{8x}$ + 7$\sqrt[]{18x}$ +28

Rút gọn biểu thức sau với x ≥ 0:
3 $\sqrt[]{2x}$ – 5 $\sqrt[]{8x}$ + 7$\sqrt[]{18x}$ +28

Share

1 Answer

  1. Lời giải:

    Với x ≥ 0 thì các căn trong biểu thức có nghĩa

    3$\sqrt[]{2x}$ -5 $\sqrt[]{8x}$ +7 $\sqrt[]{18x}$ +28

    =3$\sqrt[]{2x}$ – 5 $\sqrt[]{2^{2}.2x}$ + 7 $\sqrt[]{3^{2}.2x}$+28

    =3$\sqrt[]{2x}$ -10 $\sqrt[]{2x}$ +21 $\sqrt[]{2x}$ +28

    =14$\sqrt[]{2x}$+28

    • 0
Leave an answer

Leave an answer

Browse